Hallmarks of cellular senescence: biology, mechanisms, regulations - Amir Ajoolabady; Domenico Pratico; Suhad Bahijri; Jaakko Tuomilehto; Vladimir N. Uversky; Jun Ren (Experimental and Molecular Medicine)
Abstract Cellular senescence is a process in which the cell cycle becomes permanently arrested, thereby inhibiting cell division, proliferation and growth. Various cellular stresses, such as DNA damage, telomere shortening and oxidative stress, can trigger cellular senescence. Physiologically, cellular senescence contributes to tissue development, repair and critical biological processes such as embryogenesis, whereas, pathologically, it plays a key role in diverse disease subsets. To this end, elucidating the underlying mechanisms and molecular regulation of senescence is crucial. Here, in this Review, we explore recent key findings on cellular senescence in experimental and human disease models, focusing on its molecular mechanisms, regulation and future research directions to advance the field and facilitate therapeutic translation.